2022
DOI: 10.1111/tmi.13828
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics to support mycetoma management—Development of two target product profiles

Abstract: Objective Mycetoma is a neglected tropical disease caused by more than 70 different microorganisms and identified by the WHO as one of the high‐priority diseases for developing diagnostic tests. To ensure the production of diagnostic assays for use by clinical staff in endemic regions, target product profiles (TPPs) were designed. Methods We describe the development of two TPPs: one for a diagnostic test able to identify the causative agent of mycetoma and another that would determine when treatment could be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, the challenges in resource-limited settings for eumycetoma diagnosis are diagnostic modalities like MRI and molecular techniques are expensive, need expertise and are not readily available except in tertiary and referral centres in developing and endemic countries 6. Current serology tests available are not specific, and point-of-care tests are difficult to develop as there are more than 70 causative agents for mycetoma 7…”
Section: Discussionmentioning
confidence: 99%
“…However, the challenges in resource-limited settings for eumycetoma diagnosis are diagnostic modalities like MRI and molecular techniques are expensive, need expertise and are not readily available except in tertiary and referral centres in developing and endemic countries 6. Current serology tests available are not specific, and point-of-care tests are difficult to develop as there are more than 70 causative agents for mycetoma 7…”
Section: Discussionmentioning
confidence: 99%
“…are the most common causative agents of eumycetomas. Due to the challenges in isolating and morphologically identifying Madurella in culture media [ 4 , 9 ], many studies have reported using molecular techniques for diagnosing mycetoma [ 11 , 16 , 18 , 24 ]. Since isothermal DNA amplification techniques are regarded as a promising tool in community-based medical treatment, this study aimed to develop a LAMP method for Madurella spp.. Three primer sets were designed to target three Madurella spp.…”
Section: Discussionmentioning
confidence: 99%
“…is difficult because culture media lacks sporulation and has a slow growth rate [ 8 ]. These circumstances have become a severe diagnostic problem [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation